KINERJA PELABUHAN PERIKANAN NUSANTARA KEJAWANAN CIREBON JAWA BARAT - Agus Suherman; Herry Boesono; Faik Kurohman; Abdul Kohar Mudzakir (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
The purpose of this study is to analyze operational activities and determinants of Kejawanan Nusantara Fishing Port (NFP) performance. This research was conducted from October 2019 to March 2020 at the Kejawanan NFP. Data analysis was performed using two methods; the first is a descriptive method which is to analyze the operational activities of Kejawanan NFP and the assessment of Kejawanan NFP Performance based on guidelines issued by General Director of Capture Fisheries Number 20/KEP-DJPT/ 2015; the second is the Structural Equation Model (SEM) method, which is to define the determinants of Kejawanan NFP performance. The results of this study indicate that the operational activities of Kejawanan NFP continue to increase. Ship visits during 2019 increased by 438 times. The production value of landed fish in 2019 was Rp 147,301,194,670. Compared to 2018, production volume in 2019 decreased as many as 16.63% with the amount of 711.9 tonnes. On the other hand, production value from 2018 to 2019 also decreased by Rp 26,408,892,685. Performance assessment on 27 criterias based on guidelines issued by General Director of Capture Fisheries in 2015 showed that performance of Kejawanan NFP ranged between 70.25 and 86.5. During period of study from October 2019 to March 2020 the port showed well performances, with the best one was shown in November 2019. Based on SEM test results, internal variables have the most influence on Kejawanan NFP performance. Keywords: : Fishing Port, Kejawanan, Performance, Structural Equation Model (SEM)